The universe in a helium droplet - Volovik, G. E. (International series of monographs on physics (Oxford, England), 2009)
There are fundamental relations between three vast areas of physics: particle physics, cosmology and condensed matter physics. The fundamental links between the first two areas, in other words, between micro- and macro- worlds, have been well established. There is a unified system of laws governing the scales from subatomic particles to the Cosmos and this principle is widely exploited in the description of the physics of the early Universe. The main goal of this book is to establish and define the connection of these two fields with condensed matter physics.